2015
DOI: 10.1007/s40141-015-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Training to Optimize Learning After Traumatic Brain Injury

Abstract: One of the major foci of rehabilitation after traumatic brain injury is the design and implementation of interventions to train individuals to learn new knowledge and skills or new ways to access and execute previously acquired knowledge and skills. To optimize these interventions, rehabilitation professionals require a clear understanding of how traumatic brain injury impacts learning, and how specific approaches may enhance learning after traumatic brain injury. This brief conceptual review provides an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…A reduction in the number of targets would decrease the amount of contextual interference. Although it is well established that high contextual interference situations result in positive transfer of learning in a healthy system (Battig, 1979;MaGill & Hall, 1990;Shea & Morgan, 1979) more research is needed to identify the optimal balance of contextual interference to facilitate learning following a brain injury (Skidmore, 2015). Prior MLG studies ranged from 15 to 30 items trained at one time.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in the number of targets would decrease the amount of contextual interference. Although it is well established that high contextual interference situations result in positive transfer of learning in a healthy system (Battig, 1979;MaGill & Hall, 1990;Shea & Morgan, 1979) more research is needed to identify the optimal balance of contextual interference to facilitate learning following a brain injury (Skidmore, 2015). Prior MLG studies ranged from 15 to 30 items trained at one time.…”
Section: Introductionmentioning
confidence: 99%
“…[6] A recent Cochrane review showed that in comparison with standard physiotherapy or placebo, people who repetitively performed functional tasks showed small improvements in upper-limb function and walking. [6] Similar positive evidence has been shown for repetitive task training in people with TBI for acquiring and retaining specific skills, [7] and in people with multiple sclerosis repetitive exercise training has been shown to positively influence many outcomes including walking. [8] Providing cues to encourage, guide and praise people undergoing therapy or rehabilitation is considered a key component of therapy and is thought to improve learning.…”
Section: Introductionmentioning
confidence: 68%
“…6 3/4 studies rated as serious, 1/4 studies rated as no risk of bias and 1/5 studies rated as very serious risk of bias so overall judged to be serious risk of bias. 7 3/4 studies rated to be very serious risk of bias 8 No explanation was provided 9 7/10 studies rated as serious risk of bias, 1/10 studies rated as very serious risk of bias and 2/10 studies rated as no risk of bias…”
Section: Declarations Of Interestmentioning
confidence: 99%
“…For example, several frequently occurring pathophysiological consequences of TBI (e.g., hypoxia, seizure activity) disproportionately affect the structure and function of the hippocampus, making hippocampal damage one of the most likely consequences of injury (Tate and Bigler, 2000 ; Vespa et al, 2010 ; Atkins, 2011 ; Palacios et al, 2013 ; Sharp et al, 2014 ; Irimia and Van Horn, 2015 ). These hippocampal-dependent declarative memory deficits are of high functional significance, as they can interfere with rehabilitation efforts and community reintegration and independence following TBI (Skidmore, 2015 ).…”
Section: Introductionmentioning
confidence: 99%